2020
DOI: 10.1155/2020/7439574
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasma Sestrin2 Levels and the Presence and Severity of Coronary Artery Disease

Abstract: Aims. Atherosclerotic disease, such as coronary artery disease (CAD), is recognized to be associated with inflammation and oxidative stress. We investigated the association between CAD and plasma levels of sestrin2 which is one of the stress-inducible antioxidant proteins. Methods. We measured plasma sestrin2 levels in 304 patients undergoing elective coronary angiography. The severity of CAD was represented as the numbers of >50% stenotic coronary vessels and segments and the severity score. Results. CAD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The odds ratio for severe plaque was 5.70 (95%CI: 1.99–16.35) for a high sestrin2 level (>13.0 ng/mL). These findings demonstrated that the plasma sestrin2 levels were high in individuals with carotid plaques and were associated with the severity of carotid atherosclerosis, as reported in patients with CAD [ 39 ]. High plasma sestrin2 levels may reflect an increased oxidative stress condition and may function to help protect the body against the progression of atherosclerosis.…”
Section: Sestrin2 and Atherosclerotic Diseasessupporting
confidence: 78%
See 4 more Smart Citations
“…The odds ratio for severe plaque was 5.70 (95%CI: 1.99–16.35) for a high sestrin2 level (>13.0 ng/mL). These findings demonstrated that the plasma sestrin2 levels were high in individuals with carotid plaques and were associated with the severity of carotid atherosclerosis, as reported in patients with CAD [ 39 ]. High plasma sestrin2 levels may reflect an increased oxidative stress condition and may function to help protect the body against the progression of atherosclerosis.…”
Section: Sestrin2 and Atherosclerotic Diseasessupporting
confidence: 78%
“…Sestrin2 is suggested to be associated with aging and age-related diseases [ 12 , 36 ], and blood sestrin2 levels were reported to correlate with age [ 37 , 38 ]. Kishimoto et al also reported that plasma sestrin2 levels correlated with age (r = 0.29) in 304 patients undergoing coronary angiography [ 39 ]. Moreover, sestrin2 was demonstrated to be associated with an aging-related process, and physical exercise can upregulate sestrin2 [ 40 ].…”
Section: Sestrin2 and Cardiac Diseasesmentioning
confidence: 99%
See 3 more Smart Citations